Vagal Recovery From Cognitive Challenge Moderates Age-Related Deficits in Executive Functioning. (May 2016) - Crowley, Olga V.; Kimhy, David; McKinley, Paula S.; Burg, Matthew M.; Schwartz, Joseph E.; Lachman, Margie E.; Tun, Patricia A.; Ryff, Carol D.; Seeman, Teresa E.; Sloan, Richard P.
Decline in executive functioning (EF) is a hallmark of cognitive aging. We have previously reported that faster vagal recovery from cognitive challenge is associated with better EF. This study examined the association between vagal recovery from cognitive challenge and age-related differences in EF among 817 participants in the Midlife in the U.S. study (aged 35–86). Cardiac vagal control was measured as high-frequency heart rate variability. Vagal recovery moderated the association between age and EF (β = .811, p = .004). Secondary analyses revealed that older participants (aged 65–86) with faster vagal recovery had superior EF compared to their peers who had slower vagal recovery. In contrast, among younger (aged 35–54) and middle-aged (aged 55–64) participants, vagal recovery was not associated with EF. We conclude that faster vagal recovery from cognitive challenge is associated with reduced deficits in EF among older, but not younger individuals.